Entrepreneurship Realities in Small and Medium Enterprises in Chile: Use of Design [Realidades de Emprendimiento en Pequeñas y Medianas Empresas en Chile: Uso del Diseño] - Moreno-Munoz, C (Universidad del Zulia, 2021)
The following article presents a multimodal study, quantitative and qualitative, to compare diverse Chilean socioeconomic realities with the objective of identifying the social factors that affect the economic advance of small and medium businesses (SMBs) and limit the strategic use of Design in entrepreneurship. To carry out this analysis, the object of this study will be three Centers of Business Development (CBD) in the Metropolitan Region o Santiago, in Chile, according to the commune in which they are located and its ranking in the Index of Social Priority, which determines its socioeconomic level (low, medium and high). This will be complemented with interviews with experts of the CDB to compose a characterization of entrepreneurship in those communes. The studied realities denote a positive correlation between socioeconomic level and the degree of sophistication of CBD proposal, its strategic guidelines and the insertion of Design in their business processes. © 2021, Universidad del Zulia. All rights reserved.